Mortality Rate and Outcomes of Omicron Variant Positive Patients with Osteoporotic Fractures: A Retrospective Study - Chung, Hoe Jeong; Lee, Bum Seok; Sohn, Hoon-Sang (Journal of bone metabolism, 2024)
Background: During the lockdown period associated with the coronavirus disease 2019 (COVID-19) pandemic, increased mortality rates among patients with COVID-19 have been reported. This study aimed to analyze the mortality rate of osteoporotic hip fractures in patients who were COVID-19-positive after the lockdown during the Omicron period.Methods: A retrospective study was performed with 194 patients who were aged 70 years or more and diagnosed with osteoporotic hip fracture. The patients were divided into two groups according to their COVID-19 diagnoses. Surgery was performed within 10 days of diagnosis. Age, sex, past medical history, time until surgery, postoperative complications, and the primary outcome of mortality rate at 30 and 90 days were analyzed.Results: Among the 194 patients, 13 and 181 were in the COVID-19-positive and negative group, respectively. The total, 30-day, and 90-day mortality rates in the control and COVID-positive group were 11% and 0% (P=0.368), 1.7% and 0% (P=1.000), and 5.0% and 0% (P=1.000), respectively. No significant differences were observed in age, sex, history, time to surgery, postoperative complications, or postoperative mortality. In 1:1 propensity score matching, the time to surgery was 5.34 days in patients who were COVID-19-positive, and 3.00 days in patients who were COVID-19 negative, with no statistical significance (P=0.09). Age, sex, medical history, postoperative complications, and postoperative mortality were not significantly different between the groups.Conclusions: Regardless of the COVID-19 diagnosis, surgical treatment without delay is believed to result in positive outcomes in older patients with osteoporotic hip fractures, as no significant differences in mortality rate and respiratory complications were observed between patients who were COVID-19-positive and those who were COVID-19 negative.